2022
DOI: 10.1111/cpf.12778
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for subcutaneous fat: Does it improve the correlation between vastus lateralis echo intensity and physical performance in older women?

Abstract: Numerous studies have corrected the echo intensity of the vastus lateralis for subcutaneous fat thickness. However, it is unclear if correction for subcutaneous fat improves the correlation between vastus lateralis echo intensity and physical performance. We aimed to examine the correlations between vastus lateralis muscle morphology parameters and physical performance outcomes in older women. Twenty healthy older women (67 ± 4 years) participated in this study. Muscle cross‐sectional area, raw and corrected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The 51 included studies included 5095 (∼2759 females, ∼2301 males) participants, aged 72.5±5.8 years of age. 7,11,12,14–24,2662 Twenty-seven studies included males and females, 14,17,20,23,24,26,2830,32,33,3638,40,42,4547,49,54,5762 while 16 included only males, 7,11,15,16,18,19,21,22,31,34,39,41,48,50,52,56 seven included only females, 27,35,43,44,51,53,55 a single study did not report sex, 12 while another did not delineate sex when reporting age or participant numbers; 61 explaining the approximate values in the previous sentence. Two studies included participants with ‘metabolic syndrome’ or diabetes, 20,33 and single studies included participants with chronic obstructive pulmonary disease, 42 USA Veterans, 11 ‘frail’, 24 outpatients, 63 nursing home residents, 23 or regularly participated in competitive tennis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 51 included studies included 5095 (∼2759 females, ∼2301 males) participants, aged 72.5±5.8 years of age. 7,11,12,14–24,2662 Twenty-seven studies included males and females, 14,17,20,23,24,26,2830,32,33,3638,40,42,4547,49,54,5762 while 16 included only males, 7,11,15,16,18,19,21,22,31,34,39,41,48,50,52,56 seven included only females, 27,35,43,44,51,53,55 a single study did not report sex, 12 while another did not delineate sex when reporting age or participant numbers; 61 explaining the approximate values in the previous sentence. Two studies included participants with ‘metabolic syndrome’ or diabetes, 20,33 and single studies included participants with chronic obstructive pulmonary disease, 42 USA Veterans, 11 ‘frail’, 24 outpatients, 63 nursing home residents, 23 or regularly participated in competitive tennis.…”
Section: Resultsmentioning
confidence: 99%
“…31 Non-corrected echogenicity was used in 49 studies, 7,11,12,14–20,2224,2649,5162 while subcutaneous fat-correction was reported or obtained in 12 studies. 15,16,18,19,21,30,40,48,50,51,54,59 Both non-corrected and corrected values and/or correlations were found or obtained from 10 studies. 15,16,18,19,30,40,48,51,54,59…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations